2007
DOI: 10.1007/s00381-007-0366-x
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effects of high-dose vs low-dose melatonin after blunt sciatic nerve injury

Abstract: Our results suggest that melatonin, especially at a dose of 50 mg/kg, has a potent neuroprotective effect and can preserve peripheral neural fibers from lipid peroxidative damage after blunt trauma. With further investigations, we hope that these data may prove useful to clinicians who treat patients with nerve injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 40 publications
1
33
0
Order By: Relevance
“…Surgeries on the control group and treatment group were performed by clamping the left sciatic nerves of rats at a level 5 mm proximal to the bifurcation for 1 min using pincers with 2 mm width, and the sciatic nerves of rats in the sham-operated group were not injured (Pelled et al, 2006;Shokouhi et al, 2008).…”
Section: Surgical Operationmentioning
confidence: 99%
“…Surgeries on the control group and treatment group were performed by clamping the left sciatic nerves of rats at a level 5 mm proximal to the bifurcation for 1 min using pincers with 2 mm width, and the sciatic nerves of rats in the sham-operated group were not injured (Pelled et al, 2006;Shokouhi et al, 2008).…”
Section: Surgical Operationmentioning
confidence: 99%
“…Therefore they proposed higher doses and a longer duration of administration should be planned in experimental paradigms [2]. In line of Atik et al [2], a potent neuroprotective effect to preserve peripheral neural fibres from lipid peroxidative damage after blunt trauma achieved by Shokouhi et al [51] especially at a dose of 50 mg/kg. In our previous studies we also administered 50 mg/kg melatonin after sciatic nerve injury [22,23].…”
Section: Therapeutic Dose Of Melatoninmentioning
confidence: 95%
“…Shokouhi et al [51] investigated the neuroprotective effects of melatonin on neural fibre damage and lipid peroxidation after a blunt sciatic nerve trauma, comparing the effects of low dose (10 mg/kg) and high dose (50 mg/kg) of melatonin. According to their results, low-dose melatonin (10 mg/kg) reduced trauma-induced myelin breakdown and axonal changes in the sciatic nerve.…”
Section: Therapeutic Dose Of Melatoninmentioning
confidence: 99%
See 1 more Smart Citation
“…36 Shokouhi et al investigated the neuroprotective effects of MLT on neural fiber injury and lipid peroxidation after blunt sciatic nerve trauma; they found that a low dose reduces trauma-induced myelin breakdown and axonal changes in the sciatic nerve. 37 Stavisky et al found that a significantly higher percentage of crushed rat sciatic axons can be repaired in vitro and/or in vivo by plasmalemma fusion following exposure to MLT. 38 Erol et al observed that both MLT and octreotide gave benefits in an spinal cord injury (SCI) model, and MLT had the more pronounced beneficial effect.…”
Section: Free Radical Scavenging Effects Of Melatonin In Peripheral Nmentioning
confidence: 99%